Medication Errors (MEs) in Several Countries: A Systematic Review - Wigiyantoro, S; Surya Darmawan, E (KnE Life Sciences, 2018)
The increasing number of reports of Medication Errors (MEs) and the subsequent relevant damage, especially in the medical centres, have become a growing concern for patient safety in recent decades. Patient safety, particularly drug safety, is a major concern and the challenge for healthcare professionals around the world. Knowing the prevalence of MEs presented descriptively based on existing studies to approach systematic review. In first stages, journals were searched by using the online databases through Science Direct and EBSCO. The search used specific keywords such as ‘medication errors’ and ‘administration errors’. As a result, this study reports about Medication Errors in several countries, including two largest hospital of Isfahan in Iran, University Teaching Hospital in Korea, Mansoura Teaching University Hospital, two cases reported in Bolak Eldakror Hospital in Egypt and Midnapore Medical College and Hospital in India. Medication Errors can be prevented by various strategies, such as implementing the six rights of medication administrations principle (right patient, right medication, right dosage, right route of administration, right time and right documentation) and as a control by using a ‘double-check’ or even ‘triple check’ procedures before giving the drug to the patient. Keywords: Medication Errors (MEs), drug administration, medication administration principles